SpongeBob SquarePants. The complete ninth season [videorecording (DVD)] - Hillenburg, Stephen (Paramount, 2017)
Get ready for endless hours of nautical nonsense with the complete ninth season of SpongeBob SquarePants! Soak up over twenty tales and three double length episodes, including the latest food craze to sweep Bikini Bottom, SpongeBob's search for a new job, and a mysterious goo bubble battle!